Strategi Bisnis dan Efektivitas Sistem Informasi pada Operator Transportasi Barang Laut di Indonesia - Nur, Yunitha Ardiana; Agusinta, Lira; Kania, Dinar Dewi; Thamrin, Muhammad; Sembiring, Honny Fiva Akira (Institut Transportasi dan Logistik Trisakti, 2024)
Many studies have examined the value of strategic alignment on company’s performance in general, though the study of the information system value on other factors such as efficiency and productivity are still limited. The purpose of the study is to examine freight transportation related to its business strategy, information system strategy, Website information system effectiveness, organizational culture, and organizational effectiveness. The sample of the study was taken from 30 goods transportation companies. The data collection used 150 respondents consist of 50 academicians and 100 practitioners. The data analysis used hierarchical regression. The results show that the level of alignment of business strategy and information system affects the level of users’ satisfaction of the company’s website information system. The results also show that the level of users’ satisfaction of Web information system mediates the relationship between business strategy and information system of the company’s efficiency and productivity. The research findings do not support the role of organizational culture as a moderator of the relationship between Website information system and organizational effectiveness, although it shows the positive relationship between these variables.